Development of instrument and transformation of excellent Muslim through love of knowledge - Syaidatun Nazirah Abu Zahrin; Shahizan Shaharuddin; Nur Hidayah Mohd Abd Malik (Penerbit Universiti Kebangsaan Malaysia, 2019)
Love as a motivational factor is a driving force to excellence and transformation of human capital. Starting with the call to create a reading culture, it then developed into the generation of thoughtful culture which able to critically argues and analysis. The idea also need to be translated in the form of academical writing and disseminated to the general public so that ideas can be shared. Hence, the study reported in this paper was aimed at identifying the attributes of knowledge lover that can contribute towards excellence among Muslim youths in Malaysia. We were also interested in identifying the relationship between love of knowledge and excellence. For that reason, an instrument named as “Characteristics of Knowledge Lovers,” “Excellent Muslim” and “Transformation of Human Capital through Love for Knowledge” was created. The instrument was designed in stages. First, we analysed existing theories and concepts. Second prominent academics and students were interviewed in order to construct items for the questionnaire. Third, rater reliability was performed by asking five experts in psychology to review the items. A pilot study was then conducted to test the validity and the reliability of the questionnaire items. It was found that all of the sub-constructs are positively correlated,with the grand mean of 0.70-0.96 (very high) with significant level of p<0.01. In conclusion, the correlation between the sub-constructs are high. It is hoped that other researchers could apply the different stages of the development of the instrument in other fields.